2019
DOI: 10.3390/ani9100801
|View full text |Cite
|
Sign up to set email alerts
|

Weber’s Law and the Scalar Property of Timing: A Test of Canine Timing

Abstract: Simple SummaryUnderstanding the perceptual abilities of companion animals such as dogs adds to our understanding of the cognitive abilities of non-human animals. This study assessed the time perception abilities of dogs. In this study, dogs were required to identify whether the duration of a light was of a short or long duration by pressing a response lever. Dogs were able to correctly classify the durations as short or long. When given durations that were intermediate of the original short and long stimuli, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A finding of importance to timing research is that the point of subjective equality-the time at which choice between the two stimuli was indifferent-became smaller with changes in the discriminability of the response alternatives (Figure 7). In addition to changing with the temporal structure of the taskfor example, the geometric mean of the durations to be timed (e.g., Allan & Gibbon, 1991;Church & Deluty, 1977;Cliff et al, 2019;Fetterman & Killeen, 1991;Meck, 1983;Raslear, 1983), the duration of the inter-trial interval (Killeen & Fetterman, 1988) the PSE also changes with relative reinforcer rates for different responses (Stubbs, 1980;Machado & Guilhardi, 2000). We might have expected in the present experiment that the PSE value might simply have become poorly estimated when response discriminability became poor, but as Figure 7 shows, this was not the case: PSE values became small but were quite consistent across pigeons.…”
Section: Discussionmentioning
confidence: 99%
“…A finding of importance to timing research is that the point of subjective equality-the time at which choice between the two stimuli was indifferent-became smaller with changes in the discriminability of the response alternatives (Figure 7). In addition to changing with the temporal structure of the taskfor example, the geometric mean of the durations to be timed (e.g., Allan & Gibbon, 1991;Church & Deluty, 1977;Cliff et al, 2019;Fetterman & Killeen, 1991;Meck, 1983;Raslear, 1983), the duration of the inter-trial interval (Killeen & Fetterman, 1988) the PSE also changes with relative reinforcer rates for different responses (Stubbs, 1980;Machado & Guilhardi, 2000). We might have expected in the present experiment that the PSE value might simply have become poorly estimated when response discriminability became poor, but as Figure 7 shows, this was not the case: PSE values became small but were quite consistent across pigeons.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of the CVs with longer intervals has been noted not only in humans, but also in other animals as well. Crystal (2001) reported shallow U-shaped Weber functions for rats, as did Cliff et al (2019) in all six of the dogs they tested. Bizo et al (2006) also found it with pigeons, as shown in Figure 4.…”
Section: Contextmentioning
confidence: 91%
“…One possibility to explain these results, is that time difference between the fast and the congruent condition (0.5 s) was not large enough to be detected by dogs, while the same was not true for the time difference between the congruent and the slow conditions (1 s). This seems unlikely, as durational discrimination in dogs, as well as in other species, is based on proportional differences, rather than absolute differences (Cliff et al 2019;Heinrich et al 2022;Vanmarle and Wynn 2006). Based on that, one would expect the opposite result, since the ratio between the timing of the congruent and fast condition (3.6) was larger than that between the slow and the congruent condition (2.4).…”
Section: Discussionmentioning
confidence: 98%